Real-time PCR assay for rapid detection and quantification of Vibrio aestuarianus in oyster and seawater: A useful tool for epidemiologic studies - Saulnier, Denis; De Decker, Sophie; Haffner, Philippe (Journal of Microbiological Methods, 2009)
Because Vibrio aestuarianus is known to cause serious infections in Pacific oyster Crassostrea gigas, a real-time PCR assay was developed targeting the dnaJ gene of this bacterium. Only V. aestuarianus strains isolated from C. gigas mortality events in different geographic areas and the reference strain tested positive, whereas no amplification products was obtained with type strains belonging to 23 other species of Vibrio. Sensitivity and reproducibility of the method were assessed using either seawater or oyster homogenate samples spiked with one V aestuarianus strain. All these samples were stored at -20 degrees C in order to mimic retrospective or grouped natural sample analysis without quantification bias due to prolonged freezing. Analysis of standard curves revealed excellent correlation values between light microscopy cell enumerations and PCR Threshold Cycle (Ct) values, and acceptable PCR reaction efficiencies for all type of samples. Quantification curves of both sample types were equivalent, with a detection level as low as 1.6 V. aestuarianus cells in the PCR reaction tube, corresponding to 1.6.10(2) cells ml(-1) and 1.6.10(2) cells mg(-1) in seawater and entire oyster samples, respectively, taking into account the dilution factor used for appropriate template DNA preparation. Comparison of PCR assay reproducibility according to the complexity of samples revealed that seawater samples gave more reproducible quantification measures than samples from oyster homogenate, with precision of measured Ct values inferior to 0.4 and 0.6 respectively at 99% confidence. Use of the real-time PCR assay allowed us to monitor V. aestuarianus load in oysters naturally infected with this pathogen. Furthermore, we were able to detect V aestuarianus in samples of seawater in which oysters had been reared and in algal cultures used for feeding oysters. Because of the rapidity and reliability of the real-time PCR assay method used in this study, just a few hours are needed compared with the two days required using the ...